2023
DOI: 10.1186/s13018-023-03637-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative intra-articular steroid injections within 3 months increase the risk of periprosthetic joint infection in total knee arthroplasty: a systematic review and meta-analysis

Abstract: Objective Albeit with no disease-modifying effects, intra-articular steroid injections (IASIs) are still widely used to relieve symptoms of knee osteoarthritis. Previous literature has reported conflicting results regarding the safety of IASI in terms of periprosthetic joint infection (PJI) in total knee arthroplasty (TKA). This study tried to determine whether preoperative IASIs increased the risk of PJI, with different time intervals between the injections and surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Additionally, while there has been concern regarding potential risk for osteoarthritis progression, avascular necrosis, and articular collapse following intra-articular steroid injections, a recent study did not demonstrate this association after controlling for baseline osteoarthritis severity and pre-existing avascular necrosis/subchondral insufficiency fracture [ 40 ]. However, caution is advised and patient-specific risks should be considered in patients at greater risk of adverse outcomes, such as those who have diabetes mellitus and therefore can experience higher post-injection glycemic levels [ 41 ], as well as those already on systemic steroids [ 38 ], and those who are anticipating arthroplasty within 3 months, as this increases the risk of periprosthetic joint infection [ 42 ]. Furthermore, intra-articular injections should be avoided entirely in patients who have clinical evidence of skin or soft tissue infection overlying the target joint.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while there has been concern regarding potential risk for osteoarthritis progression, avascular necrosis, and articular collapse following intra-articular steroid injections, a recent study did not demonstrate this association after controlling for baseline osteoarthritis severity and pre-existing avascular necrosis/subchondral insufficiency fracture [ 40 ]. However, caution is advised and patient-specific risks should be considered in patients at greater risk of adverse outcomes, such as those who have diabetes mellitus and therefore can experience higher post-injection glycemic levels [ 41 ], as well as those already on systemic steroids [ 38 ], and those who are anticipating arthroplasty within 3 months, as this increases the risk of periprosthetic joint infection [ 42 ]. Furthermore, intra-articular injections should be avoided entirely in patients who have clinical evidence of skin or soft tissue infection overlying the target joint.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Albanese et al’s meta-analysis found a significant correlation between THA and PJI after corticosteroid injections, indicating a 20% increased risk for patients receiving intra-articular corticosteroids within three months before TJA [ 25 ]. However, other studies reported no discernible rise in the PJI rate due to prior intra-articular corticosteroid injections [ 76 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Despite their widespread use for diagnostic and therapeutic purposes, recent studies have reported an increased risk of infection when intra-articular injections are administered too close to elective surgeries, such as hip arthroscopy, generally within three months prior [ 4 - 8 ]. For example, a recent meta-analysis involving over 300,000 patients found that administering preoperative intra-articular steroid injections within three months of total knee arthroplasty (TKA) significantly increased the odds of periprosthetic joint infection (PJI) (P < 0.01) [ 9 ]. Similarly, another study indicated a significantly higher risk of PJI when intra-articular injections were given within three months prior to total shoulder arthroplasty (TSA), with elevated odds of infection at both three (P = 0.007) and six months (P = 0.001) postoperatively.…”
Section: Introductionmentioning
confidence: 99%